Biochemistry - Garrett, Reginald H. (Saunders College Publishing, 1999)
Intended for the one- or two-term introductory biochemistry course taught at the junior/senior level, this beautifully and consistently illustrated text gives science majors the most current presentation of biochemistry available. Written by a chemist and a biologist, the book presents biochemistry from balanced perspectives.